2017
DOI: 10.1037/pspa0000074
|View full text |Cite
|
Sign up to set email alerts
|

Social and economic ideologies differentially predict prejudice across the political spectrum, but social issues are most divisive.

Abstract: Liberals and conservatives both express prejudice toward ideologically dissimilar others . Previous work on ideological prejudice did not take advantage of evidence showing that ideology is multi-dimensional, with social and economic ideologies representing related but separable belief systems. In five studies (total N = 4912), we test three competing hypotheses of a multi-dimensional account of ideological prejudice. The dimension-specific symmetry hypothesis predicts that social and economic ideologies diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
84
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 85 publications
(159 reference statements)
18
84
3
Order By: Relevance
“…However, as stated in the social primacy hypothesis (Crawford et al, 2017), the effects for the cultural dimension should be stronger than for the economic dimension. Thus, in Study 1 we measured political beliefs, the perception of value violation, and attitudes toward a range of groups.…”
Section: Overview Of the Studiesmentioning
confidence: 91%
See 2 more Smart Citations
“…However, as stated in the social primacy hypothesis (Crawford et al, 2017), the effects for the cultural dimension should be stronger than for the economic dimension. Thus, in Study 1 we measured political beliefs, the perception of value violation, and attitudes toward a range of groups.…”
Section: Overview Of the Studiesmentioning
confidence: 91%
“…In this vein, Crawford et al (2017) demonstrated that cultural and economic beliefs differentially predict prejudice toward groups with dissimilar beliefs. They showed that indeed the two dimensions of political beliefs independently predict attitudes toward groups on the other side of the political spectrum (dimensionspecific symmetry hypothesis).…”
Section: Structural Complexity Of Political Beliefsmentioning
confidence: 98%
See 1 more Smart Citation
“…Rokeach (1954) argued that tendencies toward rigidity and authoritarianism were present in extreme partisans of both the left and the right. Research inspired by this ideological symmetry view has shown that several mechanisms supposedly distinctive of conservatism operate across ideological differences with equivalent intensity, such as tough-mindedness (Eysenck, 1956), dogmatism (Rokeach, 1954), motivated reasoning (Taber & Lodge, 2006) and prejudice (Brandt, Reyna, Chambers, Crawford, & Wetherell, 2014;Crawford, Brandt, Inbar, Chambers, & Motyl, 2017). Specifically addressing selective exposure, Frimer et al analyzed individuals' unwillingness to engage in a crosscutting ideological conversation and found that ideology does not significantly moderate this effect (Frimer, Skitka, & Motyl, 2017, see Figure 6).…”
Section: Is Selective Exposure Bipartisan?mentioning
confidence: 99%
“…Conservatives tend to express prejudice toward groups perceived as liberal, and liberals tend to express prejudice toward groups perceived as conservative. This is because these groups hold values that are in opposition (Crawford, Brandt, Inbar, Chambers, & Motyl, 2017; Wetherell, Brandt, & Reyna, 2013). I also included a measure of perceived conventionalism as an alternative, less direct measure of value dissimilarity on the political dimension.…”
mentioning
confidence: 99%